Implementasi Media Tanaman Pisang Untuk Peningkatan Perkembangan Motorik Halus Anak Usia Dini - Ani Malisa; Dwi Nomi Pura; Syisva Nurwita (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to determine whether the implementation of banana plant-based media—such as banana fruit, stems, and leaves—in the learning process can enhance the fine motor skill development of early childhood children aged 4–5 years. This study employed classroom action research. The subjects were 15 children from Group A at PAUD Cita Ananda, Kelindang Village. The results showed that: (1) teacher activity improved from a score of 50 (73.5%, categorized as